Occurrence of Surface Active Agents in the Environment - Ewa Olkowska; Marek Ruman; Żaneta Polkowska (Journal of Analytical Methods in Chemistry)
Due to the specific structure of surfactants molecules they are applied in different areas of human activity (industry, household). After using and discharging from wastewater treatment plants as effluent stream, surface active agents (SAAs) are emitted to various elements of the environment (atmosphere, waters, and solid phases), where they can undergo numerous physic-chemical processes (e.g., sorption, degradation) and freely migrate. Additionally, SAAs present in the environment can be accumulated in living organisms (bioaccumulation), what can have a negative effect on biotic elements of ecosystems (e.g., toxicity, disturbance of endocrine equilibrium). They also cause increaseing solubility of organic pollutants in aqueous phase, their migration, and accumulation in different environmental compartments. Moreover, surfactants found in aerosols can affect formation and development of clouds, which is associated with cooling effect in the atmosphere and climate changes. The environmental fate of SAAs is still unknown and recognition of this problem will contribute to protection of living organisms as well as preservation of quality and balance of various ecosystems. This work contains basic information about surfactants and overview of pollution of different ecosystems caused by them (their classification and properties, areas of use, their presence, and behavior in the environment).